Assessing biological invasions in European Seas: Biological traits of the most widespread non-indigenous species. (5th February 2018) - Cardeccia, Alice; Marchini, Agnese; Occhipinti-Ambrogi, Anna; Galil, Bella; Gollasch, Stephan; Minchin, Dan; Narščius, Aleksas; Olenin, Sergej; Ojaveer, Henn
Abstract: The biological traits of the sixty-eight most widespread multicellular non-indigenous species (MWNIS) in European Seas: Baltic Sea, Western European Margin of the Atlantic Ocean and the Mediterranean Sea were examined. Data for nine biological traits was analyzed, and a total of 41 separate categories were used to describe the biological and ecological functions of these NIS. Our findings show that high dispersal ability, high reproductive rate and ecological generalization are the biological traits commonly associated with MWNIS. The functional groups that describe most of the 68 MWNIS are: photoautotrophic, zoobenthic (both sessile and motile) and nektonic predatory species. However, these 'most widespread' species comprise a wide range of taxa and biological trait profiles; thereby a clear "identikit of a perfect invader" for marine and brackish environments is difficult to define. Some traits, for example: "life form", "feeding method" and "mobility", feature multiple behaviours and strategies. Even species introduced by a single pathway, e.g. vessels, feature diverse biological trait profiles. MWNIS likely to impact community organization, structure and diversity are often associated with brackish environments. For many traits ("life form", "sociability", "reproductive type", "reproductive frequency", "haploid and diploid dispersal" and "mobility"), the categories mostly expressed by the impact-causing MWNIS do not differ substantially from the whole set of MWNIS. Graphical abstract: Highlights: We analysed nine biological traits of the most widespread NIS in European seas. We looked for similar biological trait profiles amongst the 68 most widespread NIS. Three major profiles emerged: photoautotrophic, zoobenthic and nektonic species. Many widespread NIS are benthic iteroparous invertebrates with pelagic larva. Several widespread NIS feature multiple categories of feeding and mobility.